Dancing with Dionysus: the myth of Leucippus and "Daphne" by Richard Strauss and Joseph Gregor - Díaz Gito, Manuel Antonio (Amaltea. Revista de Mitocrítica, 2016)
First part of a two-section article that analyses the extensive reinterpretation of Daphne’s myth in the opera Daphne (1938) by composer Richard Strauss and librettist Joseph Gregor, who used the version of the myth by Parthenius of Nicaea better than that by Ovid. Itsultimate aim is to examine Strauss’ statement about his new opera’s meaning and if the authors managed to achieve their objective by means of manipulating the mythical storyline.